The Influence of Capital Adequacy, Asset Quality and Liquidity on the Profitability of Bank Jateng: Pengaruh Kecukupan Modal, Kualitas Aset dan Likuiditas Terhadap Profitabilitas Bank Jateng - Clarisa Apri Damayanti; Edy Purwanto; Sukamto (LPPM Universitas Pelita Bangsa, 2025)
For stakeholders who wish to evaluate a company's financial accounts, the ratio's computation is crucial. The study's goal is to examine how Bank Jateng's profitability is impacted by the capital adequacy ratio, asset quality, and liquidity. Data gathering is a review of the literature with the goal of locating information and data in electronic documents that can aid in the writing process. According to the data analysis's findings, Bank Jateng's profitability was not significantly impacted by either the liquidity ratio, as determined by the Loan Deposit Ratio (LDR), or the capital adequacy, as determined by the Capital Adequacy Ratio (CAR). The profitability of Bank Jateng was significantly impacted by the asset quality ratio as determined by the Non-Performing Loan (NPL). The CAR ratio can be used by bStakeholders who wish to evaluate a company's financial accounts, the ratio's computation is crucial. The study's goal is to examine how Bank Jateng's profitability is impacted by the capital adequacy ratio, asset quality, and liquidity. Data gathering is a review of the literature with the goal of locating information and data in electronic documents that can aid in the writing process. Bank Jateng's profitability was not significantly impacted by either the liquidity ratio, as determined by the Loan Deposit Ratio (LDR), or the capital adequacy, as determined by the Capital Adequacy Ratio (CAR). The profitability of Bank Jateng was significantly impacted by the asset quality ratio as determined by the Non-Performing Loan (NPL). The CAR ratio can be used by businesses to safeguard depositors and enhance the stability and effectiveness of the financial system.usinesses to safeguard depositors and enhance the stability and effectiveness of the financial system. Pihak-pihak yang ingin menilai laporan keuangan suatu perusahaan, perhitungan rasio sangat penting. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana rasio kecukupan modal, kualitas aset, dan liquiditas berdampak pada profitabilitas Bank Jateng. Studi pustaka mengarahkan pencarian data dan informasi melalui dokumen elektronik yang dapat mendukung dalam proses penulisan untuk pengumpulan data. Rasio kecukupan modal (CAR) dan rasio liquiditas (LDR) yang diukur melalui rasio deposito pinjaman (LDR) tidak berdampak signifikan terhadap profitabilitas Bank Jateng. Sebaliknya, rasio kualitas aset yang diukur melalui rasio pinjaman yang tidak memenuhi syarat (NPL) berdampak signifikan terhadap profitabilitas Bank Jateng. Perusahaan dapat menggunakan rasio CAR untuk melindungi deposan dan meningkatkan stabilitas serta efisiensi sistem keuangan.